2013
DOI: 10.1080/13803395.2013.844773
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging correlates of everyday action in dementia

Abstract: The everyday, functional impairments associated with dementia remain poorly understood from a neuropsychological perspective. This study investigated relations between brain structure volumes and two measures of everyday action – caregiver questionnaire and direct assessment – in 57 participants with dementia. Results showed that caregiver ratings reflecting more functional impairment were strongly associated with smaller volumes of deep white matter. Direct assessment of everyday task performance in a subsamp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
15
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 73 publications
(96 reference statements)
6
15
1
Order By: Relevance
“…Of note, although the two performance-based measures significantly correlated with each other, neither of these measures correlated significantly with the informant-report of IADLs. This is consistent with previous findings of limited correlations between questionnaire and performance-based measures of functional status (e.g., Siedel, in press; Kempen, Steverink, Ormel, & Deeg, 1996; Reuben, Valle, Hays, & Siu, 1995; Schmitter-Edgecombe et al, 2011). In a recent study (Schmitter-Edgecombe et al, 2011), it was suggested that questionnaire and performance-based measures of everyday functioning may tap into different aspects of everyday functioning; that is, knowledge gained from multiple experiences in everyday situations and the individual’s application of everyday problem-solving skills, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…Of note, although the two performance-based measures significantly correlated with each other, neither of these measures correlated significantly with the informant-report of IADLs. This is consistent with previous findings of limited correlations between questionnaire and performance-based measures of functional status (e.g., Siedel, in press; Kempen, Steverink, Ormel, & Deeg, 1996; Reuben, Valle, Hays, & Siu, 1995; Schmitter-Edgecombe et al, 2011). In a recent study (Schmitter-Edgecombe et al, 2011), it was suggested that questionnaire and performance-based measures of everyday functioning may tap into different aspects of everyday functioning; that is, knowledge gained from multiple experiences in everyday situations and the individual’s application of everyday problem-solving skills, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…That is, the MCI and OA control groups differed significantly in the number of task parts omitted (not completed) but not in the number of task parts executed inaccurately. This is consistent with recent research that has shown that omission errors are associated with cognitive correlates of episodic memory in individuals with MCI (Schmitter-Edgecombe & Parsey, 2014, and with smaller volume in the hippocampus and medial temporal lobe in dementia patients (Bailey, Kurby, Giovannetti, & Zacks, 2013;Giovannetti, Bettcher, Brennan, Libon, Kessler, et al, 2008;Seidel et al, 2013). Consistent with a role for memory in Amap Task execution, better memory skills as represented by MAS list learning were associated with higher Amap execution accuracy scores for the MCI group.…”
Section: Discussionsupporting
confidence: 91%
“…E-mail: tgio@temple.edu. functioning and omissions with episodic memory and global cognition (Giovannetti et al, 2008, see also Giovannetti et al, 2012), and with distinct brain regions (Bailey, Kurby, Giovannetti, & Zacks, 2013;Seidel et al, 2013), suggesting that these error components are the result of separate underlying processes.…”
Section: Introductionmentioning
confidence: 97%